Incidence of cervical collar-related pressure injury in patients with head and neck trauma: A scoping review study - Mohammad Behnammoghadam; Nasrollah Alimohammadi; Ali Riazi; Maryam Eghbali-Babadi; Majid Rezvani (Wolters Kluwer Medknow Publications, 2023)
The use of the cervical collar to support the head and neck is inevitable in many patients with head and spinal cord injuries. One of the consequences of using this instrument is the development of pressure injuries. Therefore, in this review study, the incidence of as well as the risk factors for cervical collar-related pressure injury in this group of patients was evaluated. The current study is a scoping review conducted in 2022. Five scientific databases (PubMed, Scopus, Web of Science, ProQuest, and CINAHL), as well as Google Scholar, were searched for relevant studies published from 1990 to 2022 using the following keywords: trauma, spinal cord injury, head injury, head trauma, collar, cervical collar, cervical immobilization, risk factors, incidence, pressure injury, pressure ulcer, and bed sore. The search was performed independently by two researchers. Articles from the initial search were first recorded in special tables, and then, were reviewed and analyzed separately by two researchers. After extraction, information from each article was entered into a special table categorized by year, country, study design, study population, the incidence of cervical collar-related pressure injury, risk factors for cervical collar-related pressure injury, and grades of pressure injury. Of the 10 articles, 6 were retrospective cohort studies, 3 were cross-sectional descriptive studies, and 1 was a case report study. In terms of the study population, one study was conducted on pediatric patients, one was conducted on elderly patients, and eight were conducted on adults with head and neck trauma. In eight articles, the incidence of cervical collar-related pressure injury was reported. The reported incidence varied between 1.1% and 78.4%. In eight articles, risk factors for cervical collar-related pressure injury were reported. The most common risk factors were duration of cervical collar use, hospitalization in intensive care units, low level of consciousness, and longer hospital stay. The current review study showed that a significant percentage of head and neck trauma patients for whom cervical collar is used suffer from different grades of pressure injuries. Hence, healthcare providers should consider this issue when caring for this group of patients and take the necessary preventive measures in this regard. It should be noted that previous studies in this field had significant limitations, and thereby, it is strongly recommended to conduct further studies with a stronger methodology.